Assessing the possibilities of filling the gap between Romania and the EU in the RDI field - Steliana Sandu; Cristian Paun (Romanian Academy, National Institute for Economic Research, 2010)
In the specialised literature there are several established models and methods for measuring the time required to fill the gap between various systems, by assessing the rate of development required to reach a certain reference level in a determined period of time. These models are known as “catching-up models”. The purpose of this study is the assessment, based on such models, of the pace required to fill the gap between Romania and the EU in the R&D field as well as of the factors that condition the pace required to achieve convergence with EU-25 average.
Keywords: I28; F15; I21; H52; 330; catching-up models; gap filling; RDI public private funding